Cold stratification complements cold water in enhancing the germination of Juniperus procera seeds - Lemessa, Debissa; Lemessa, Debissa; Negussie, Hailu; Melesse, Seid; Didita, Motuma (Current Botany, 2017)
Enhancing seed germination is a fundamental step for conservation of plant genetic resources but less is understood specifically for endangered native and endemic tree species in the tropics. We examined how cold stratification and application of different treatments impact the germination of Juniperus procera seeds. We collected seeds from nine different altitudes of Managesha forest, Oromia region, Ethiopia. The seeds were stored in gene bank at -10oC for four years for cold stratification as a dormancy breaking method. We employed three treatments: cold water, 70oC hot water and 100 ml of 1% H2O2 to setup germination experiment in completely randomized design with four replications (50 seeds each). The germinated seeds were counted every fifth day until no more germinated seeds were observed. We analyzed data using two-way ANOVA and the significant for mean difference among altitudinal gradients was computed with Tukey HSD tests. The germination percent from cold stratified and moistened in cold water was higher than either from control, soaking in 70oC hot water or applying 1% H2O2 solution. Moreover, the germination percent varied among the altitudinal gradients for all the three treatments. At some altitudes, the germination was higher or lower consistently throughout control and the three treatments. The variations in altitudinal gradient and the associated environmental factors have triggered the differences in germinability of J. procera seeds. Our overall results suggest that cold stratification can complement cold water to break the dormancy and enhance the germination of J. procera seeds.